Emergency management of temporomandibular joint dislocation with manual reduction - Abidin, Zefry Zainal; Baehaqi, Ronny (Hasanuddin University, 2019)
Objective:Present serial case management of temporomandibular joint dislocation in emergency unit and to provide information on emergency handling in the case of temporomandibula joint especially for dentist.Method: Datas of temporomandibular joint dislocation cases were collected from October 2016 to March 2017 with a cross sectional study presented by Oral and Maxillofacial Resident in RSUD Dr Soetomo Surabaya.Results: Nine patients were managed. In totalmales accounted for 66,67% of the patients, and yawning was the most frequent etiological factor. Acute TMJ dislocation had the highest frequency in this study. The management conducted was giving muscle relaxant, manual repositioning and head bandage. Manual reduction of TMJ dislocation can be divided into three approaches, intraorally, extraorally and a combination between the two approaches; intraorally by using Hippocrates’ technique and Wrist Pivot technique. The extraoral approach does not involve fingers in the oral cavity. Applying these three approaches could be distinguished by clinical examination and patient history.Conclusion: Temporomandibular joint dislocation is one of the problem in dentistry that requires direct management and could cause complications if immediate treatment is not givenKeywords: Dislocations, Manual Reduction , Temporomandibular joint